Integrating vocational training in culinary arts and Islamic studies at juvenile rehabilitation centres: Malaysian experience - Esa, Ahmad; Abd. Aziz, Z. S.A.A.; Mohd Salleh, B.; Mohamad,, N. H. (2017)
The Juvenile Rehabilitation Centres (JRC) in Malaysia aims to provide shelter, counselling and skills training to juveniles specifically for those who wish to transform themselves from the regrettable misdeeds they have committed. At JRCs, an integrated Culinary Vocational Training and Islamic education forms part of their training curriculum. The skills acquired should enable trainees to secure jobs upon completion of training. However, there are some training institutions that lack systematic training structures resulting in trainees becoming less skilful in both vocational and Islamic education. The objective of this research is to identify the effectiveness of an integrated Culinary and Islamic Education curriculum implemented at JRCs in Malaysia. This is a descriptive survey and data was obtained using questionnaire and interview. Respondents comprised 92 trainees, four managers, four culinary trainers and four Islamic education teachers, all from four different JRCs. The findings show that the trainees are happy with their trainings that brought about positive effects for them. Some suggestions have been made to provide improvements in the implementation of the course among them the inclusion of prayers in the Islamic education syllabus.